Microsnare-Assisted Mechanical Removal of Intraprocedural Distal Middle Cerebral Arterial Thromboembolism - Fourie, Pieter; Duncan, Ian C. (American Journal of Neuroradiology, 2003)
Thromboembolic events are potential complications of neurointerventional procedures. The mainstay of therapy for these complications is both supportive therapy and the use of fibrinolytic agents. In some cases, the occluding clot seems to be resistant to fibrinolytic or anti-platelet agents. We herein report our successful attempt at clot removal by using a microsnare to mechanically capture and remove a small resistant organized clot fragment that was occluding one of the post-trifurcation M2 divisions of a middle cerebral artery. This complication occurred during coil embolization of an ipsilateral posterior communicating aneurysm.